Tracing Darwin's Path in Cape Horn - Rozzi, Ricardo, 1960-; Massardo, Francisca; Heidinger, Kurt (Book collections on Project MUSE., 2018)
"Book is bilingual in English and Spanish. It is about the early explorations of Cape Horn, the southernmost tip of South America, and the discoveries by Charles Darwin during his three trips to the area"--Provided by publisher